PENGARUH METODE ACTIVE KNOWLEDGE SHARING SELAMA PANDEMI COVID-19 TERHADAP HASIL BELAJAR SISWA KELAS VII IPS SMPN BEKUNGIN BEKASI (Jurnal Sosial Humaniora dan Pendidikan, 2022)
When a pandemic occurs, it finally makes us learn how to learn and teach student. One of them is the online and offline model. Conditions during the pandemic are not allowed face-to-face learning in class, so it is only allowed in small groups. The strategy of mapping the area adjacent to where you live and then grouping it can be the right choice. Active Knowledge Sharing learning method is a cooperative learning activity and then group members share tasks with each other to solve problems. Through the Active Knowledge Sharing learning method, it is hoped that each student can provide input to other group members according to their experience and knowledge. The Active Knowledge Sharing method can encourage students' motivation to be more active and will be able to..encourage..students..to..improv..mastery..of the..material. Sharing experiences with fellow group members and sharing with the whole class will motivate students to learn. So the..Active..Knowledge.Sharing learning.method is a..cooperative learning activity, students are placed in heterogeneous groups and then group members share tasks with each other to solve problems. Through the Active Knowledge Sharing learning method, it is hoped that each student can provide input to other group members according to their experience and knowledge.